The Effect of Liquidity, Leverage and Company Size on Company Value with Corporate Social Responsibility as a Mediating Variable - Kristantiningtyas, Dhian; Dewi, Maria Rosa Kumala (Institut Bisnis dan Informatika Kesatuan, 2024)
This research aims to analyze the influence of liquidity, leverage and company size on company value with corporate social responsibility as a mediating variable. The liquidity variable is proxied by current ratio, the leverage variable is proxied by debt to equity ratio, the company size variable is proxied by the Natural Log of assets, the company value variable is proxied using Tobin's Q while the corporate social responsibility (CSR) uses assessment aspects from Global Reporting Initiatives (GRI) using 78 items. This type of research is quantitative research with a purposive sampling method with 148 samples from 64 mining and agricultural sub sector companies listed on the Indonesia Stock Exchange. This subsector was chosen because this subsector is closely related to the surrounding environment. The analytical method used is mediation regression analysis using the program, SmartPLS. The results of the hypothesis testing analysis show that liquidity, leverage and company size do not influence company value with CSR as a mediating variable. Testing the mediation effect also shows that the CSR variable is unable to mediate the relationship between liquidity, leverage and company size and company value. This means that the profits earned by the company are mostly used for the company's internal interests. The company also carries out CSR as a form track of social responsibility towards the environment which is not affected by the company's finances.